Assets Holding and Financial Performance of Pension Fund Administrators in Nigeria - Ogungbade, Oluyinka Isaiah; Igbekoyi, Olusola Esther; Efuntade, Alani Olusegun; Efuntade, Omotayo Olubunmi; Olaniyan, Niyi Oladipo (Acta Universitatis Danubius. Œconomica, 2022)
Pension funds are established to guarantee that contributors get a monthly or lump amount of income upon retirement. The financial performance of pension funds in Nigeria appears to be riddled with uncertainty, risk, and delays in the distribution of the benefits, creating concerns about their ability to meet its main goal. Pension Fund Managers in Nigeria were subjected to this research in order to determine the link among assets held and financial organizational performance. A total of 21 PFAs were investigated as part of this investigation, which used judgmental sampling. Secondary data from PFAs was used in the research. Specifically, the information gathered refers to investments in asset classes, and the investment reports on dividends, interest, and rental revenue. The data was evaluated using correlational statistics to assess whether or not there is a statistically significant difference between the asset classes and the components of investment income in question. Assessments of the relationship between the composition of the various pension fund portfolios and the amount of the various asset classes in relation to the amount of investment income earned were also carried out in order to determine whether diversification of the portfolio has an impact on the financial performance of the pension funds. According to the findings of the study, the accumulation of assets by the PFAs has an impact on the financial performance of the pension funds. From the findings of this study, it is obvious that the assets held by PFAs are favorably and statistically relevant in terms of their financial performance. Consequently, it is vital for PFAs to assess the asset mix in the fund management process to avoid over-exposure to any one asset.